DEVELOPING READING TEXT MATERIALS FOR VOCATIONAL SCHOOL - Femy Septiani and Busmin Gurning (REGISTER: Journal of English Language Teaching of FBS-Unimed, 2014)
This study concerns on how reading text materials are developed for vocational school. This study was conducted by using developmental research. The subject of this research was class XII SMK Sandhy Putra 2 Medan consisting of 36 students. Instrumentations for collecting data were questionnaire and interview. After analyzing the data, the writer got the students’ need in learning English in term of vocation that they have. Based on the students’ need analysis, then it was got some basic competences which need to be reached by the students, and based on the basic competences, syllabus can be designed. After syllabus had been designed, developing teaching materials was done. The developed teaching materials were related to the vocation that the students had; it was culinary art. The development of materials followed four stages; those were pre-development/ planning, development, evaluation, and revision.